Recombinant Human Cytomegalovirus Expressing an Analog-Sensitive Kinase pUL97 as Novel Tool for Functional Analyses - Krämer, Nadine; Schütz, Martin; Mato, Uxía Gestal; Herhaus, Lina; Marschall, Manfred; Zimmermann, Christine (Viruses, 2022)
The human cytomegalovirus (HCMV) is a member of the beta-herpesvirus family and inflicts life-long latent infections in its hosts. HCMV has been shown to manipulate and dysregulate many cellular processes. One major interactor with the cellular host is the viral kinase pUL97. The UL97 gene is essential for viral replication, and kinase-deficient mutants of pUL97 display a severe replication defect. Recently, another group established an analog-sensitive version of the pUL97 protein. This mutant kinase can be treated with a non-hydrolysable ATP analog, thereby inhibiting its kinase function. This process is reversible by removing the ATP analog by media change. We introduced this mutant version of the pUL97 protein into the laboratory strain Ad169 of HCMV, BADwt, creating a BAD-UL97-as1 viral mutant. This mutant virus replicated normally in infected cells in the absence of the ATP analog and maintained its ability to phosphorylate its cellular substrates. However, when treated with the ATP analog, BAD-UL97-as1 displayed a defect in the production of intra- and extracellular viral DNA and in the production of viral progeny. Furthermore, in the presence of 3MB-PP1, a well-established substrate of pUL97 was no longer hyperphosphorylated. This effect was detectable as early as 4 h post treatment, which allows for studies on pUL97 without the complication of low viral titers. Nevertheless, we observed off-target effects of 3MB-PP1 on several cellular processes, which should be considered with this approach.
CRIS-Team Scopus Importer:2022-11-04
Keywords: analog-sensitive pUL97 variant; BACmid-derived recombinant HCMV; functional analyses; human cytomegalovirus (HCMV); protein kinase pUL97; pUL97-specific inhibitors; viral kinase activity